Inorganic materials in hollow carbon nanostructures - Botos, Ákos (2016)
The interactions of metal-containing molecules and nanoparticles (NPs) with the interior of hollow graphitic carbon nanostructures (CNs) were investigated and their chemical transformations in the nanoscale channels of CNs appraised. The gas phase insertion of Group VI metal hexacarbonyl complexes (M(CO)6, M=Cr, Mo, W) into CNs was successfully developed and optimised to provide good filling rates as confirmed by transition electron microscopy (TEM). Infrared (IR) and Raman spectroscopy demonstrated that Group VI M(CO)6 complexes with greater polarisability exhibit stronger van der Waals interactions with the interior of single walled carbon nanotubes (SWNTs). The synthesis of metal based NPs inside graphitised carbon nanofibers (GNFs) by the in situ transformation of the encapsulated M(CO)6 precursor molecules was successfully achieved and it was demonstrated that GNFs can act as a source of oxygen in these reactions. The nanotube filling methodology was applied for the multi-step synthesis of new inorganic materials inside CNs by the controlled reactions of M(CO)6, I2 and H2S. This approach yielded unusual van der Waals hybrid materials such as “tube inside a tube” and other hybrid structures of MoS2 and GNFs. In SWNTs, with significantly narrower diameters than GNFs or multi-walled carbon nanotubes (MWNTs), metal complexes form unique 1D arrays of octahedral [M6I14]2- clusters with the nanotube acting as a nanocontainer and a poly-cation balancing the charge of the guest-clusters. The iodides of Mo and W were effectively converted into extremely thin MS2 nanoribbons (NRs) within SWNTs, providing a new more efficient route to the hybrid inorganic nanostructures. In MWNTs, the [Mo6Ii8Ia2Ia a4/2] clusters are packed in a hexagonal pattern to optimise filling of the void, and when reacted with H2S they provide a range of multi-layered MS2NRs with their widths controlled by the internal diameter of the host nanotube.